ASSOCIATION BETWEEN MIDDLE TURBINATE PNEUMATIZATION AND SUPERIOR ATTACHMENT OF THE UNCINATE PROCESS ON COMPUTED TOMOGRAPHY (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of uncinate process attachment to the lamina papyracea and to analyze its association with concha bullosa on computed tomography.Subjects and Methods: A cross-sectional analytic study was conducted on 150 patients (300 nasal sides) at Nhan Dan Gia Dinh Hospital from June 2024 to June 2025. The presence of concha bullosa and SAUP types (classified by Landsberg & Friedman) were evaluated on multiplanar CT scans. Because both nasal sides from the same patient may be anatomically correlated, the association was analyzed using logistic regression with generalized estimating equations (GEE). Odds ratios (ORs) with 95% confidence intervals (95% CIs) were reported.Results: Concha bullosa was identified in 33.7% of nasal sides. The most common uncinate process attachment was to the lamina papyracea (type 1), accounting for 53.3%. Analysis revealed that the prevalence of type 1 attachment in the CB group (48.5%) was comparable to that in the non-CB group (55.8%). GEE analysis showed no statistically significant association between concha bullosa and Type 1 attachment of the uncinate process (OR = 0.74; 95% CI: 0.46–1.21; p = 0.229).Conclusion: In this study, concha bullosa was not significantly associated with the superior attachment pattern of the uncinate process. These findings do not support a mechanical compression effect of concha bullosa on uncinate attachment. Therefore, both structures should be evaluated independently on multiplanar CT for safe surgical planning.
Keywords: Concha bullosa, uncinate process, superior attachment, computed tomography